2018
DOI: 10.3389/fimmu.2018.02658
|View full text |Cite
|
Sign up to set email alerts
|

Novel Treatments in Lupus

Abstract: Purpose of Review: The standard treatment options for systemic lupus erythematosus (SLE) are focused on non-specific immunosuppression. Over the past few years, scientific studies and ongoing clinical trials have shifted the paradigm with rapid advances in developing biologics and small molecules. A number of monoclonal antibodies and small molecule inhibitors have been developed to target specific pathways involved in SLE. Many of these novel therapeutic agents are already being tested in clinical trials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 109 publications
(114 reference statements)
0
30
0
Order By: Relevance
“…IFNA2 is primarily produced by dendritic cells (38). This cytokine is targeted as a treatment for the autoimmune disease, systemic lupus erythematosus (39). Exposure to INFA2 has been linked to causing edema and been shown to induce the production of cytokine IL-7 (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…IFNA2 is primarily produced by dendritic cells (38). This cytokine is targeted as a treatment for the autoimmune disease, systemic lupus erythematosus (39). Exposure to INFA2 has been linked to causing edema and been shown to induce the production of cytokine IL-7 (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…During the active stage of SLE, CD40L is abnormally overexpressed by CD4 + T and CD8 + T cells. [ 31 ] Preclinical studies showed that transgenic mice ectopically expressing CD40L on B cells developed lupus-like disease. Meanwhile, lupus-prone NZB/W mice delayed the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for SLE may include a combination of antimalarials with a glucocorticoid such as prednisone (64). In the context of COVID-19, steroid use as a prophylaxis or treatment has been controversial through several conflicting studies.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…IL-2 agonists have great potential in T cell manipulation, as they have a strong ability to redirect the host immune system towards tolerance by the upregulation of Tregs (64). In several clinical trials in SLE patients (66,67), low-dose IL-2 therapy was shown to have strong potential of expanding Treg populations (68).…”
Section: Il-2 Agonistsmentioning
confidence: 99%
See 1 more Smart Citation